MnO4(3-) NIR luminescence in Ba2SiO4 - Ferracin, L. C.; Davolos, Marian Rosaly [UNESP]; Nunes, LAO (Elsevier B.V., 1997)
Ba2SiO4: MnO43- luminescence is reported and compared to similar host lattices based on PO43-, VO43- and AsO43-, where Mn5+ substitutes for p(5+),V5+ Or AS(5+). The observed energy position of MnO43- 1E state in SiO44- is in accordance with interelectronic repulsion caused by Mn5+-O bond length. At 77 K the E-1 splitting is 119 cm(-1), which is in agreement with 1.8 degrees, the average deviation of O-M-O angles from the regular tetrahedron. These values are adjusted to Ca point symmetry. The vibronic-structure spectra evidenced a progression with a frequency assigned to the nu(2)(E) bending mode of MnO43-.
Keywords: Barium orthosilicate; Mn5+; NIR luminescence; Barium compounds; Crystal lattices; Ions; Manganese compounds; Near infrared luminescence; Luminescence